Penerapan PSAK 105 Tentang Akad Mudharabah Pada BMT Mandiri Sejahtera Jawa Timur Gresik - Novita Ati (SUSTAINABLE JURNAL AKUNTANSI, 2023)
ABSTRACTMudharabah financing is a form of cooperation between the owner of the fund (shohibul maal) who provides the funds, and the fund manager (mudharib) as the manager of the business with profits divided according to the agreement at the beginning of the agreement. The purpose of this study was to determine how to recognize, measure, and present transactions for mudharabah financing based on PSAK 105 at BMT Mandiri Sejahtera, East Java. The method in this research used descriptive qualitative research. Data collection techniques in this study with interviews and documentation. Data analysis was carried out by descriptive analysis by comparing the accounting treatment of mudharabah financing applied to BMT Mandiri Sejahtera, East Java. The findings of the study indicated that the accounting treatment of mudharabah financing at BMT Mandiri Sejahtera East Java has been able to apply PSAK 105 correctly and is in accordance with the accounting treatment of mudharabah financing which consists of recognition, measurement and presentation. It's just that when acknowledging the investment, the BMT recognizes it as a mudharabah financing, not a mudharabah investment. And the profit sharing of mudharabah financing is not fully in accordance with PSAK 105, because the BMT has determined from the beginning the profit sharing is not from the results of bargaining for the results between the BMT and customers or members.Keywords: Mudharabah Financing, PSAK 105, BMT Mandiri Sejahtera East Java